PELATIHAN PEMBUATAN MEDIA PEMBELAJARAN BERUPA ALAT PERAGA KARTU BILANGAN PECAHAN DI SD NEGERI KASATRIYAN - Novy Trisnani (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2019)
Training is one way to improve the quality of teachers to be able to prepare, manage, and implement the learning process according to the applicable curriculum by utilizing the facilities and infrastructure as much as possible. Community Service Activities (PPM) aims to broaden the knowledge and skills of community service participants in developing learning media in the form of fraction card teaching aids. The subjects of this study were classroom teachers and mathematics teachers at SD Negeri Kasatriyan. The method of carrying out PPM activities includes presentation of material, training in making media/props, and evaluation. From the evaluation results of PPM activities it can be concluded: 1) PPM activities are useful and meaningful for all devoted participants, 2) in the practice process of making media/teaching materials, the devotee participants do not experience significant difficulties, and 3) more than 75% of devotion participants provide positive response to PPM activities.Keywords: Training, Number Card, Media